PENGARUH PUPUK HAYATI DAN BAHAN ORGANIK TERHADAP POPULASI DAN BIOMASSA CACING TANAH PADA PERTANAMAN BAWANG MERAH (Allium ascalonicum L) DI KECAMATAN MERBAU MARATAM KABUPATEN LAMPUNG SELATAN - Annove Kurnia Arofi; Sri Yusnaini; Kus Hendarto; Mas Achmad Syamsul Arif (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
This study aimed to determine the effect of biofertilizer, organic matter and the interaction between biofertilizer and organic matter on population, biomass of earthworm and shallot production. This experiment was conducted in Merbau Mataram, South Lampung Regency on September – December 2017, designed by using Randomize Block Design (RBD) with two factors, i.e. : Biofertilizer application consists of biofertilizer and non biofertilizer and organic matter application consists of chicken manure, cow manure, oyster mushroom baglog and straw compost. Analysis of variance (anova) was carried out using a significance level of 0,05 after verifying the additivity (Tukey’s test) and homogeneity of variance (Bartlett’s test) of the data. When a significant effect was revealed in the anova, the mean separations among treatments were obtained by least significant difference (LSD 0.05). The results showed that application of biofertilizer (Bio max grow) increased earthworm population in 37 days after planting at 10 – 20 cm depth and 70 days after planting at 0 – 10 and 10 – 20 cm depth, biofertilizer application also affected earthworm biomass and shallot production in 70 days after planting. Oyster mushroom application gave the best effect compared to the other organic matter on population and biomass of earthworm and shallot production.